Vasoconsrictive and vasodilatative imbalance at experimental fecal peritonitis - Savytskyi, I. V.; Tsypoviaz, S. V.; Lenik, R. G.; Balytska, H. O.; Bilash, O. V.; Zashchuk, R. H.; Miastkivska, I. V. (Journal of Education, Health and Sport, 2019)
Peritonitis problem today one of the most urgent issues in the field of clinical pathological physiology and abdominal surgery. According to various data, mortality in peritonitis is 18.3 - 62.8%. Endothelial dysfunction is the main cause of cardiovascular diseases and death in patients after postponed peritonitis.The aim of the study – investigation of vasoconstrictive and vasodilatative potential in the pathogenesis of experimental peritonitis and its correction.It has been proved that experimental fecal peritonitis development pathologically affects the vessels functional state at each of the research stages. It's established weakening of the vasodilatative process on the background of peritonitis development, as evidenced by a decrease in the content of S-nitrosothiols. Result of this work has been proved that in peritonitis pathogenesis the vasoconstrictor potential of the vessels is significantly increased, as evidenced by a significant increase in endothelin-1 in animals that have been modeled by fecal peritonitis. Nitric oxide donor efficiency has been proved as part of complex correction of peritonitis and endothelial dysfunction as its complication. The most pronounced positive effect was detected at the 21st day, which indicates the expediency of long-term use of L-arginine as a remedy for correction.